1994
DOI: 10.1557/jmr.1994.1761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of precursors on the combustion synthesis of TiC-Al2O3 composite

Abstract: In the combustion synthesis of TiC-Al2O3 composites from TiO2, Al, and C, different types of precursors, i.e., anatase and rutile TiO2, and graphite and carbon black were used. The measurements of combustion wave velocity showed that the reactivity was higher with graphite as a carbon source and anatase as a TiO2 source. This was also confirmed by analyzing the degree of conversion of reactants to products. For the precursors investigated, the wave propagation of the 3TiO2-4Al-3C system diluted by A12O3 showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Since the starting TiO 2 phase has the anatase modification, the presence of rutile in the quenched-reaction zone is an indication of a solid-solid transformation of titania, a process that takes place at 918 K. The presence of titanium in this zone is consistent with the two-step mechanism mentioned above and is in agreement with reports in the literature. 3,12,13 The differential thermal analysis (DTA) study by Sundaram et al 16 on the system 4Al⅐3TiO 2 has shown that the reaction between Al and TiO 2 at 1165 K leads to the formation of Ti 3 Al according to…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the starting TiO 2 phase has the anatase modification, the presence of rutile in the quenched-reaction zone is an indication of a solid-solid transformation of titania, a process that takes place at 918 K. The presence of titanium in this zone is consistent with the two-step mechanism mentioned above and is in agreement with reports in the literature. 3,12,13 The differential thermal analysis (DTA) study by Sundaram et al 16 on the system 4Al⅐3TiO 2 has shown that the reaction between Al and TiO 2 at 1165 K leads to the formation of Ti 3 Al according to…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the Ti 3 Al phase is also believed to take place before the primary combustion reaction. This suggestion is based on the observation of AlTi 3 in DTA experiments which are done typically at a much lower heating rate than that experienced in SHS. Another justification for this proposal is based on previous observations on the synthesis of TiC/Ni-Al composites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower temperature is sufficient for grain growth, but is below the ignition temperature of 900°C which is commonly found for pressed pellets in the formation of composites of titanium carbide and alumina from TiO 2 , C, and Al. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Differential thermal analysis was performed on selected powders using approximately 30 mg samples which were heated up in either a nitrogen or argon atmosphere to 1200°C at a heating rate of 20°Cиmin −1 using a Shimadzu DTA-50 instrument. Thermogravimetric analysis was also performed using the same parameters in a Shimadzu TGA-50.…”
Section: Methodsmentioning
confidence: 99%